Audit Sistem Informasi Pada Sistem Antrismecone Untuk PPDB Menggunakan Framework IT-IL V3 - Iwan Haryatno; Arifah Budi Hidayah; Dede Ari Putragani; Nurul Afifah; Jeffri Prayitno Bangkit Saputra (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The “AntriSmecone” queuing system was implemented in the PPDB process at SMK Negeri 1 Purwokerto to improve efficiency by up to 70%. However, the system encountered several issues, such as race condition conflicts in queue numbers and code execution errors caused by automatic translation. This study employs the IT-IL V3 framework, focusing on the Service Operation domain to analyze IT service management, particularly in the subdomains of incident management and request fulfillment. The research methodology includes interviews, observations, questionnaire distribution, and literature studies. The analysis results indicate that the system's maturity level is at level 4 (Managed and Measurable), with an average score of 3.74. The system has structured and monitored procedures, allowing deviations to be effectively addressed. Recommendations were formulated to optimize incident management and fulfill user requests. This study contributes to the development of the “AntriSmecone” system to ensure service quality and efficiency in the PPDB process.